HUBUNGAN PEKERJAAN DAN PENGETAHUAN IBU YANG MENGGUNAKAN PUMPING DENGAN KEBERHASILAN ASI EKSKLUSIF DI PUSKESMAS ULEE KARENG KOTA BANDA ACEH TAHUN 2023 - Ula, Zahratul; Mauliati, Desria; Saudah, Saudah; Susanti, Dewina; Ulfah, Ulfah; Wuskiya, Urwatun; Suriyanti, Suriyanti (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Around 44% of infants aged 0-6 months worldwide were exclusively breastfed during the 2015-2020 period out of the 50% exclusive breastfeeding target according to WHO. The low level of exclusive breastfeeding will impact the quality and livability of the next generation. Globally in 2019, 144 million toddlers are estimated to be stunted, 47 million are estimated to be underweight and 38.3 million are overweight or obese. Research Objective to determine the relationship between work and knowledge of mothers who use pumping with the success of exclusive breastfeeding at the Ulee Kareng Health Center, Banda Aceh City. Research Methods The technique used in sampling is Non Probability sampling technique with incidental sampling type with a total sample of 72 people. The research instrument was a questionnaire. Data analysis using univariate and bivariate analysis with the SPSS statistical program. The results of statistical tests with the Chi-Square test showed a p-value of 0.071> 0.05, so there was no relationship between the work of mothers who used pumping with the success of exclusive breastfeeding at the Ulee Kareng Health Center, Banda Aceh City in 2023. The statistical test results with the Chi-Square test showed a p-value of 0.001 <0.05, so there was a relationship between the knowledge of mothers who used pumping with the success of exclusive breastfeeding at the Ulee Kareng Health Center, Banda Aceh City in 2023. Conclusion There is no relationship between the work of mothers who use pumping with the success of exclusive breastfeeding at the Ulee Kareng Health Center, Banda Aceh City in 2023. There is a relationship between the knowledge of mothers who use pumping with the success of exclusive breastfeeding at the Ulee Kareng Health Center, Banda Aceh City in 2023.